Bridging Tourism and Healthcare: The Impact of Service Quality, Waiting Time, and Patient Expectations On Traveller Satisfaction in Bali - Jean Andrina Liem; Vicia Gloria; Meiriyanti Dhita Nur Afifa; Clara Sembiring (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study examines the influence of service quality, facilities, waiting time, and patient expectations on healthcare traveller satisfaction in Bali, a leading global tourism destination where casual medical needs frequently arise. As international travel increases, so does the demand for accessible, efficient, and high-quality healthcare services for tourists experiencing common illnesses or requiring administrative medical support. Using a modified 19-item SERVQUAL-based questionnaire, data were collected from 138 international travellers who received care at a private clinic in Pecatu, Bali. Reliability and validity testing demonstrated strong psychometric properties (Cronbach’s Alpha = 0.899; all items above r-table 0.361). Moderated Regression Analysis (MRA) was applied to evaluate both direct and interaction effects. Results show that the model explains 59% of the variance in satisfaction (R² = 0.590). Service quality exhibited the strongest positive direct effect on satisfaction (p < 0.001), while facilities showed an unexpected negative direct effect, and waiting time had no significant direct impact. Patient expectations demonstrated a significant negative effect and played a crucial moderating role. High expectations weakened the positive effect of service quality while strengthening the influence of facilities and waiting time on satisfaction. These findings underscore that traveller satisfaction is shaped not only by operational performance but also by the psychological standards tourists bring to their healthcare encounters. The study contributes to expectancy-disconfirmation theory in medical tourism and emphasizes the need for transparent communication, standardized service delivery, modern facility enhancements, and strategic expectation management. Strengthening these areas will support Bali’s competitiveness as a trusted and efficient healthcare destination for international travellers.